PENGARUH PROFITABILITAS, LEVERAGE, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2019 - Efrida Siboro; Hendra F. Santoso (Jurnal Akuntansi, 2021)
This study aims to determine the effect of profitability, leverage and capital intensity on tax avoidance, that is proxied by return on assets, debt to equity ratio, capital intensity ratio and cash effective tax rate (CETR). This research is a quantitative study. The type of data used is secondary data obtained from BEI’s official website. The Samples in this research are property and real estate companies listed on Indonesia Stock Exchange period 2016-2019 while selected by purposive sampling method. The analysis method used is multiple regression analysis using SPSS 24 software. The results showed that (1) profitability with a return on asset measuring instrument had a significant negative effect on cash effective tax rate, (2) Leverage had no effect on on cash effective tax rate and (3) Capital Intensity had a significant positive effect on the cash effective tax rate.   Keywords: profitability, leverage, capital intensity, return on assets, cash effective tax rate (CETR).